Exploring lignification in conifers by silencing hydroxycinnamoyl-CoA:shikimate hydroxycinnamoyltransferase in Pinus radiata - Wagner, Armin; Ralph, John; Akiyama, Takuya; Flint, Heather; Phillips, Lorelle; Torr, Kirk; Nanayakkara, Bernadette; Te Kiri, Lana (Proceedings of the National Academy of Sciences - PNAS, 2007)
The enzyme hydroxycinnamoyl-CoA:shikimate hydroxycinnamoyltransferase (HCT) is involved in the production of methoxylated monolignols that are precursors to guaiacyl and syringyl lignin in angiosperm species. We identified and cloned a putative HCT gene from Pinus radiata, a coniferous gymnosperm that does not produce syringyl lignin. This gene was up-regulated during tracheary element (TE) formation in P. radiata cell cultures and showed 72.6% identity to the amino acid sequence of the Nicotiana tabacum HCT isolated earlier. RNAi-mediated silencing of the putative HCT gene had a strong impact on lignin content, monolignol composition, and interunit linkage distribution. AcBr assays revealed an up to 42% reduction in lignin content in TEs. Pyrolysis-GC/MS, thioacidolysis, and NMR detected substantial changes in lignin composition. Most notable was the rise of p-hydroxyphenyl units released by thioacidolysis, which increased from trace amounts in WT controls to up to 31% in transgenics. Two-dimensional ¹³C-¹H correlative NMR confirmed the increase in p-hydroxyphenyl units in the transgenics and revealed structural differences, including an increase in resinols, a reduction in dibenzodioxocins, and the presence of glycerol end groups. The observed modifications in silenced transgenics validate the targeted gene as being associated with lignin biosynthesis in P. radiata and thus likely to encode HCT. This enzyme therefore represents the metabolic entry point leading to the biosynthesis of methoxylated phenylpropanoids in angiosperm species and coniferous gymnosperms such as P. radiata.